Development on coiled tubing fracturing sleeve for shale gas horizontal well. (May 2017) - Guan, Feng; Miao, Zhipeng; Zhou, Chuanxi; Xu, Jian; Wan, Feng; Liu, Shaohu; Yang, Ting; Wu, Jiwei
According to the conventional well cementing method, the cementing sliding sleeve, as a key part of the casing, needs to be opened by switch tool step by step to conduct fracture with coiled tubing. However, it usually needs switch tool to locate accurately, which is indeed a challenge. This article proposes a set of fracturing sliding sleeve with six-opening-degree and hydraulic switch tool working with coiled tubing–enabled fracturing sliding sleeve. The three-dimensional models, finite element analysis, and flow analysis of the tool are also adopted, which can validate the rationality of the tool's structure. The experimental tests show that the sliding sleeve can be opened or closed with multi-opening degree easily and overcome the gas coning, which can fully meet the requirements of down-hole operation. In addition, the switch tool can open or close the sliding sleeve under lower pressure, and it has a high success rate to open or close the sliding sleeve by coiled tubing without precision location.